2022
DOI: 10.1038/s41598-022-21322-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of alkannin/shikonin biosynthesis in response to jasmonate and salicylic acid in Lithospermum officinale

Abstract: Alkannin/shikonin and their derivatives are specialised metabolites of high pharmaceutical and ecological importance exclusively produced in the periderm of members of the plant family Boraginaceae. Previous studies have shown that their biosynthesis is induced in response to methyl jasmonate but not salicylic acid, two phytohormones that play important roles in plant defence. However, mechanistic understanding of induction and non-induction remains largely unknown. In the present study, we generated the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…For example, Wang et al (2014) demonstrated that the application of methyl jasmonate (MeJA) on shikonin-deficient A. euchroma cell lines rapidly led to the overexpression of several genes involved in the biosynthesis of A/Sd, including PGT , but was not accompanied by a significant higher production of A/Sd. In another study, Ahmad et al (2022b) showed a significantly higher expression of LePGT1 , LePGT2 , and LeGHQH1 in Lithospermum officinale L. roots treated with MeJA, but no higher accumulation of total A/Sd, after eight weeks. Conversely, the same authors ( Ahmad et al, 2022a ) demonstrated that the bacterium Chitinophaga sp.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, Wang et al (2014) demonstrated that the application of methyl jasmonate (MeJA) on shikonin-deficient A. euchroma cell lines rapidly led to the overexpression of several genes involved in the biosynthesis of A/Sd, including PGT , but was not accompanied by a significant higher production of A/Sd. In another study, Ahmad et al (2022b) showed a significantly higher expression of LePGT1 , LePGT2 , and LeGHQH1 in Lithospermum officinale L. roots treated with MeJA, but no higher accumulation of total A/Sd, after eight weeks. Conversely, the same authors ( Ahmad et al, 2022a ) demonstrated that the bacterium Chitinophaga sp.…”
Section: Discussionmentioning
confidence: 88%
“…Firstly, it is not excluded that the duration of Experiment 1 (37 days) was too short to result in a significant increased production of A/Sd, or that the timing of plant harvesting in our experiments was not optimal (i.e., gene expression behavioral oscillations due to the plant circadian cycle) ( Merrow et al, 2005 ). The PGT s regulate the first biosynthetic steps forming the basic carbon skeleton that leads to A/Sd, and therefore, it is possible that the resulting modulation of A/Sd production took longer after the upregulation of the relative expression of target PGT genes, as supported by Ahmad et al (2022b) , or that the genes oscillations were not timely targeted during our harvest times, as suggested by Wang et al (2014) ( Figure 6 ). Secondly, in a study by Andrade et al (2013) , a mismatch between alkaloid levels, another important SM group, and gene expression was reported in different Catharanthus roseus (L.) G. Don tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a consistent promotional effect for shikonin biosynthesis in L. erythorhizon, A. euchroma [21], L. officinale [62], and O. paniculatum [63]. Exogenous MeJA promoted the accumulation of shikonin derivatives, shikonofuran derivatives, and rosmarinic acid in the shikonin-proficiency cells, and caused a rapid and massive increase in the expression of genes involved in the shikonin biosynthesis pathway, such as HMGR and PGT [21].Zhao et al [16,31] overexpressed LeMYB1 in hairy roots of L. erythorhizon.…”
Section: 4shikonin Synthesis Of Aehr Under Nh4+ Toxicity and Its Poss...mentioning
confidence: 87%
“…Studies have shown a consistent promotional effect of shikonin biosynthesis in L. erythorhizon, A. euchroma [21], L. officinale [62], and O. paniculatum [63]. Exogenous MeJA promoted the accumulation of shikonin derivatives, shikonofuran derivatives, and rosmarinic acid in shikonin-proficiency cells and caused a rapid and massive increase in the expression of genes involved in the shikonin biosynthesis pathway, such as HMGR and PGT [21].…”
Section: Shikonin Synthesis In Aehr Under Nh 4 + Toxicity and Its Pos...mentioning
confidence: 90%